Paddle boat with wooden oars - Mumbai Archive Project Team (Jio Institute, 2024)
Rakesh Bhalia has been a fisherman for 35 years. Before running a motorboat, he operated paddle boats with wooden oars. He still relies on oars when navigating through mangroves and shallow waters near the shore. Underwater rocky outcrops can easily damage a wooden boat if not navigated carefully.